The current “competent” school, under the ethical impasse between (only) instrumentalizing or humanizing in the mediation with the Information and Communication Digital Technologies (Research, Society and Development, 2020)
This paper has a predominantly qualitative approach and is of a reflexive epistemological character about the use of Information and Communication Technologies - ICT, in the school space from the authors' experiences. We conducted a critical review of the authors dealing with the theme, in the neoliberal educational context. The following text deals with the use of Information and Communication Technologies - ICT, today TDIC, increasingly occupying the school space. Looking at a past tense marked by “magistrocentric” and instructional teaching practices, which are still resistant, we diagnose an ever greater “pressure” suffered by the school, so that it is “modern” - like other social facilities, for example, companies. We point out the need for the teacher to invest in continuing education, as long as it does not result in hurried adaptations just to account for a “technical competence” emptied of a more profound, integral and humanized “reading of the world” (Freire), as “Political competence” (Saviani). Hence, we point to the need for a synthesis between instrumentalization and humanization in mediation with TDIC. We concluded that just an “ethics of adaptability” (Pereira) to the new technocentric scenario and revolutionized by communications is not enough. Our hypothesis: if the school fails to translate the teacher-student relationship - central focus of the approach - as action by subjects (Severino) protagonists of a mediation with their territories of intersubjective experiences, the school runs the risk of being only “modern ”, But not“ re-enchanted ” (Assmann) and much less humanized.